Technical Language Barriers and Engineering Communication Challenges Among Marine Engine Officers: Implications for STCW Certification and Onboard Safety Performance - Marudut Bernadtua Simanjuntak; Ardiansyah; Natanael Suranta (Department of Marine Engineering, Institut Teknologi Sepuluh Nopember, 2026)
The engine room represents one of the most technically demanding and communicatively complex environments in maritime operations, yet engineering communication among marine engine officers remains substantially underexplored relative to the well-documented study of bridge communication. This study investigates technical language barriers and engineering communication challenges among marine engine officers within Indonesian maritime institutions, examining their implications for STCW certification outcomes and onboard safety performance. Using a mixed-methods design incorporating a validated technical communication assessment rubric, structured questionnaires, and semi-structured interviews with 115 participants comprising marine engineering educators, engineering cadets, and certified engine officers, the study identifies a pronounced proficiency deficit in machinery-related technical language, particularly in watch handover protocols and emergency engineering communication. Quantitative findings reveal that engineering cadets achieve an overall mean proficiency score of 2.05 on a four-point scale aligned with STCW Chapter III competency standards, falling within the Developing range across all four communication domains assessed. Qualitative analysis attributes this deficit to the dominance of Bahasa Indonesia as the medium of technical instruction, the absence of engineering-specific communication simulation, and a systemic disconnect between language training and technical training programs. The study contributes a theoretically grounded assessment framework specific to engine room communication and advances evidence-based recommendations for curriculum integration, simulator-based pedagogy, and regulatory quality assurance in Indonesian maritime engineering education.